Single-cell RNA sequencing combined with whole exome sequencing reveals the landscape of the immune pathogenic response to chronic mucocutaneous candidiasis with STAT1 GOF mutation - Lu, Xiaodi; Zhang, Keming; Jiang, Weiwei; Li, Hang; Huang, Yue; Du, Mingwei; Wan, Jian; Cao, Yanyun; Du, Lin; Liu, Xiaogang; Pan, Weihua (Frontiers in Immunology, 2022)
Chronic mucocutaneous candidiasis (CMC) is characterized by recurrent or persistent infections with Candida of the skin, nails, and mucous membranes (e.g., mouth, esophagus, and vagina). Compared with that of other infectious diseases, the immune pathogenic mechanism of CMC is still poorly understood. We identified a signal transducer and activator of transcription 1 gain-of-function (c.Y289C) mutation in a CMC patient. Single-cell transcriptional profiling on peripheral blood mononuclear cells from this patient revealed decreases in immature B cells and monocytes. Further analysis revealed several differentially expressed genes related to immune regulation, including RGS1, TNFAIP3, S100A8/A9, and CTSS. In our review of the literature on signal transducer and activator of transcription 1 gain-of-function (c.Y289C) mutations, we identified seven cases in total. The median age of onset for CMC (n=4, data lacking for 3 cases) was 10.5 years (range: birth to 11 years), with an average onset age of 8 years. There were no reports linking tumors to the c.Y289C mutation, and the incidence of pre-existing clinical disease in patients with the c.Y289C mutation was similar to previous data.